2022
DOI: 10.1155/2022/3035073
|View full text |Cite
|
Sign up to set email alerts
|

An Immunity-Associated lncRNA Signature for Predicting Prognosis in Gastric Adenocarcinoma

Abstract: Background. Gastric adenocarcinoma (GAD) is one of the most common tumors in the world and the prognosis is still very poor. Objective. We sought to identify reliable prognostic biomarkers for the progression of GAD and the sensitivity to drug therapy. Method. The RNA sequencing data of GAD was downloaded from the Cancer Genome Atlas (TCGA) database and used for analysis. Differentially expressed, immune-related lncRNA (DEIRlncRNA) was characterized by differential analysis and correlation analysis. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Although it is often assumed that pseudogenes lack function, recent studies have shown that they can have key roles, functioning as antisense, interference or competing endogenous transcripts [ 79 81 ]. RP11-115H13.1 was one of only eight lncRNAs identified as associated with a high risk of gastric cancer [ 82 ], but the dataset analysed in this study contained both male and female samples, meaning the prognostic value of RP11-115H13.1 in male patients was likely underestimated. To our knowledge, there are no existing reports of the potential cellular function of RP11-115H13.1 or ARSFP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is often assumed that pseudogenes lack function, recent studies have shown that they can have key roles, functioning as antisense, interference or competing endogenous transcripts [ 79 81 ]. RP11-115H13.1 was one of only eight lncRNAs identified as associated with a high risk of gastric cancer [ 82 ], but the dataset analysed in this study contained both male and female samples, meaning the prognostic value of RP11-115H13.1 in male patients was likely underestimated. To our knowledge, there are no existing reports of the potential cellular function of RP11-115H13.1 or ARSFP1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is often assumed that pseudogenes lack function, recent studies have shown that they can have key roles, functioning as antisense, interference or competing endogenous transcripts (Pink et al ., 2011; Kovalenko and Patrushev, 2018; Cheetham, Faulkner and Dinger, 2020). RP11-115H13.1 was one of only eight lncRNAs identified as associated with a high-risk of gastric cancer (Zhao et al ., 2022), but the dataset analysed in this study contained both male and female samples, meaning the prognostic value of RP11-115H13.1 in male patients was likely underestimated. To our knowledge, there are no existing reports of the potential cellular function of RP11-115H13.1 or ARSFP1.…”
Section: Discussionmentioning
confidence: 99%